Appendicitis and Pregnancy: Report of Two (2) Cases - Issa, Ouedraogo; Boubakar, Toure; Alexis, Sawadogo Yobi; Sibraogo, Kiemtoré; Rodrigue, Sib Sansan; Hyacinthe, Zamané; Moussa, Sanogo; Blandine, Tieba-Bonane (International Journal of Current Innovations in Advanced Research, 2023)
A cute appendicitis is a common pathology with an estimated lifetime incidence of 7 % to 8 %. However, during pregnancy, its incidence is much lower, ranging from 0.05 % to 0.13 %. It is the most common non-obstetrical surgical emergency during pregnancy. It is a serious condition in pregnancy because of delay in diagnosis leading to complications with a poorer maternal and fetal prognosis. The purpose of this study is to discuss the specific diagnostic features of acute appendicitis in pregnancy to facilitate early diagnosis and improve its management. We report such two cases of appendicular peritonitis: first of a 28-year-old woman, diagnosed during the first trimester of pregnancy and the second of 21 years diagnosed during the caesarean section. For pregnant women exhibiting abdominal pain in the right iliac fossa, right flank or right hypochondriac regions associated with fever and vomiting, acute appendicitis should be suspected in time to avoid complications leading to poor maternal and fetal prognosis.